Elaboration of a collective brand: the case of Kiriri de Barreiras indigenous tribe (Emancipação, 2023)
The Kiriri indigenous people, located in Barreiras, has been looking for forms of organization, partnerships and income generation to benefit the community. So, with the creation of Association of Small Rural Indigenous Producers Kiriri de Barreiras, the community has been involved in projects aimed at learning about the manufacture and use of native fruits of the Cerrado biome for the manufacture of jellies, sweets and other artisanal products. In addition, indigenous tribe also works with the manufacture of clay items, using traditional techniques and various handicrafts. One of the objectives of the community is to establish a better management organization that allows the commercialization of its products. In this context, the present work aimed to develop a collective brand and visual identity, aiming to protect the products or services to be implemented. In this article, the step-by-step instructions for carrying out the work and the perspectives for its continuity are presented.
Keywords: Collective Brand. Intellectual property. Cerrado fruits.